The comparative performance of lightweight green wall media for the removal of xenobiotic organic compounds from domestic greywater. (1st August 2022) - Abd-ur-Rehman, H.M.; Deletic, A.; Zhang, K.; Prodanovic, V.
Highlights: Removal of XOCs was higher using carbonaceous waste materials as compared to natural minerals. Polar hydrophilic XOC showed highest removal using zeolite. Low solubility and hydrophobic XOCs were best removed using coco coir. Mixing zeolite with coco coir is recommended to remove wider range of XOCs. Retention time of greywater in green wall should match the adsorption kinetics of XOCs. Abstract: Green walls can provide an aesthetic approach to treat domestic greywater in urban landscapes. However, the widespread adoption of green walls for greywater treatment depends on its performance to remove the emerging contaminants from greywater such as xenobiotic organic compounds (XOCs). In this study, the performance of five lightweight green wall media types (zeolite, perlite, date seeds, coffee grinds, and coco coir) was evaluated for the removal of six XOCs representing a range of hydrophilic to hydrophobic organic micropollutants in domestic greywater (acetaminophen, diethyltoluamide, bisphenol A, oxybenzone, triclosan, nonylphenol). The adsorption affinity of targeted XOCs on different green wall media types, the role of contact time on XOCs removal, and the impact of background pollutants in greywater matrix on the adsorption of XOCs were analysed. Results indicate that removal of XOCs was higher using carbonaceous waste materials (date seeds, coffee grinds, and coco coir) as compared to natural minerals (zeolite and perlite). Moreover, the adsorption of XOCs increased with the increase in pollutant hydrophobicity. All XOCs showed highest removal using coco coir with fast adsorption kinetics, achieving 90% of the removal in 30 min. The only exception was acetaminophen that showed best removal using zeolite but exhibited slow adsorption kinetics with 90% of the removal attained in 24 h. The initial adsorption kinetics (<30 min) of XOCs in greywater were adversely affected by the presence of background pollutants, indicating the need of higher residence time of greywater in green wall system for better removal of XOCs. Based on the findings of this batch study, it is recommended to design a green wall system with more than 30 min of greywater residence time using a mixture of coco coir and zeolite for effective removal of XOCs from domestic greywater. Graphical abstract: Image, graphical abstract